External Dacryocystorhinostomy Under Local Anesthetia - Yasir Iqbal, Qaim Ali Khan, Sohail Zia (Pakistan Journal of Ophthalmology, 2016)
Purpose: To document the results of External dacryocystorhinostomy (EX-DCR) under Local Anesthesia with sedation for treatment of nasolacrimal duct (NLD) obstruction. Study Design: Interventional study case series. Place and duration of Study: conducted at a private clinic in Gilgit Pakistan over a 3 year period. Materials and Methods: Data was prospectively collected on all patients who underwent EX-DCR. The Indication for surgery was a blocked nasolacrimal duct obstruction. Patients underwent irrigation of the nasolacrimal drainage systems, fluorescein dye disappearance test, and intranasal examination. Patients with previous dacryocystorhinostomy surgery to the same eye were excluded from the study. EX-DCR was performed under local anesthesia with sedation on outpatient basis by a single surgeon having expertise in the technique. Follow up was at day 1, 1st week and on 6th month for. During postoperative visits, patients were asked about symptomatic resolution of epiphora and assessed with patency on irrigation, fluorescein dye disappearance test, and intranasal examination. All patients were followed up for at least 6 months. Surgical success was defined by patient’s resolution of symptoms with patency on irrigation. Results: 61 patients were included in the study with a mean age of 37.16 ± 12 years. Most of the operated patients were females (77.05%) with a nearly equal distribution between left and right eyes. Intraoperative complications were unable to suture posterior flap (4.92%), excessive bleeding above 100ml in one patient, snipping of puntum one patient and unable to pass DCR tube in one patient. None of the patients had uncontrolled intranasal bleeding, cardiovascular event or local anesthesia toxicity during the surgery. All of the patients had a successful outcome which was determined by patent syringing. The most common Post-operative complication was ecchymosis in 14.75%. Conclusion: In order to avoid the risks of General anesthesia, EX-DCR under LA with sedation is a safe and highly effective alternative technique in terms of surgical outcome. Key Words: Dacryocystorhinostomy, local anesthesia, nasolacrimal duct obstruction.